Elimination of LRVs Elicits Different Responses in Leishmania spp - Saura, Andreu; Zakharova, Alexandra; Klocek, Donnamae; Gerasimov, Evgeny S; Butenko, Anzhelika; Macedo, Diego H; Servienė, Elena; Zagirova, Diana; Meshcheryakova, Anastasia; Rogozin, Igor B; Serva, Saulius; Kostygov, Alexei Yu; et al. (mSphere, 2022)
Leishmaniaviruses (LRVs) have been demonstrated to enhance progression of leishmaniasis, a vector-transmitted disease with a wide range of clinical manifestations that is caused by flagellates of the genus Leishmania. Here, we used two previously proposed strategies of the LRV ablation to shed light on the relationships of two Leishmania spp. with their respective viral species (L. guyanensis, LRV1 and L. major, LRV2) and demonstrated considerable difference between two studied systems. LRV1 could be easily eliminated by the expression of exogenous capsids regardless of their origin (the same or distantly related LRV1 strains, or even LRV2), while LRV2 was only partially depleted in the case of the native capsid overexpression. The striking differences were also observed in the effects of complete viral elimination with 2'C-methyladenosine (2-CMA) on the transcriptional profiles of these two Leishmania spp. While virtually no differentially expressed genes were detected after the LRV1 removal from L. guyanensis, the response of L. major after ablation of LRV2 involved 87 genes, the analysis of which suggested a considerable stress experienced even after several passages following the treatment. This effect on L. major was also reflected in a significant decrease of the proliferation rate, not documented in L. guyanensis and naturally virus-free strain of L. major. Our findings suggest that integration of L. major with LRV2 is deeper compared with that of L. guyanensis with LRV1. We presume this determines different effects of the viral presence on the Leishmania spp. infections. IMPORTANCE Leishmania spp. represent human pathogens that cause leishmaniasis, a widespread parasitic disease with mild to fatal clinical manifestations. Some strains of leishmaniae bear leishmaniaviruses (LRVs), and this has been shown to aggravate disease course. We investigated the relationships of two distally related Leishmania spp. with their respective LRVs using different strategies of virus removal. Our results suggest the South American L. guyanensis easily loses its virus with no important consequences for the parasite in the laboratory culture. Conversely, the Old-World L. major is refractory to virus removal and experiences a prominent stress if this removal is nonetheless completed. The drastically different levels of integration between the studied Leishmania spp. and their viruses suggest distinct effects of the viral presence on infections in these species of parasites.
Keywords: virové plášťové proteiny; capsid; Leishmania; Leishmaniasis; leishmanióza; LRV1; lidé; LRV2; Capsid Proteins; Leishmania guyanensis; Leishmania major; Leishmaniavirus; Humans